The Influence of Riko the Series on the Learning Outcomes of the Water Cycle for Elementary School Students - Angga, Wahyu Septi; Aeni, Ani Nur; Karlina, Dety Amelia (FKIP Universitas Lampung, 2023)
Abstract: This research aims to determine the impact of the Riko the Series on the learning outcomes of elementary school students in the water cycle material. The learning outcomes referred to in this study pertain to the achievement at the level of conceptual understanding in the cognitive domain. This is a quantitative study with quasi-experimental research as its method. The research utilizes a Nonequivalent Control Group design, involving pretest and posttest assessments in each group, with the population being all fourth-grade students of elementary school of Negeri Sukaraja 1. The sampling technique used is purposive sampling The sample consists of 31 students from Class IV A and 31 students from Class IV B, both from elementary school of Sukaraja 1. The preliminary findings indicate a significant impact on the learning outcomes of elementary school students in the water cycle material, whether or not the Riko the Series is used. Subsequent research findings reveal that the learning approach involving the Riko the Series leads to better learning outcomes, as evidenced by higher average scores. However, when comparing the learning outcomes between the experimental and control groups, no significant impact is found. To measure the influence in more detail, an effect size calculation is performed. The result of the effect size calculation, based on Cohen's D criteria, considering the entire population of fourth-grade students at elementary school of Negeri Sukaraja 1 Sumedang, suggests that the Riko the Series has a low impact on the learning outcomes of elementary school sukaraja 1 Sumedang with an effect size of 0.254. Keywords: riko the series, elementary school, water cycle Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh Riko the Series terhadap hasil belajar siswa sekolah dasar pada materi siklus air. Hasil belajar yang dimaksud dalam penelitian ini adalah pencapaian pada tingkat pemahaman konsep dalam ranah kognitif. Penelitian ini merupakan penelitian jenis kuantitatif dengan kuasi eksperimen sebagai metode penelitiannya. Dalam penelitian ini, digunakan desain Nonequivalent Control Group, yang melibatkan pengujian pretest sebelum perlakuan dan pengujian posttest setelah perlakuan di setiap kelompok, populasi dalam penelitian ini adalah seluruh siswa kelas IV SD Negeri Sukaraja 1 teknik pengambilan sampel menggunakan purposive sampling dengan sampel 31 siswa kelas IV A SD Negeri Sukaraja 1 dan 31 siswa kelas IV B SD Negeri Sukaraja 1. Hasil penelitian awal menunjukkan adanya pengaruh yang signifikan terhadap hasil belajar siswa sekolah dasar pada materi siklus air, baik saat Riko the Series digunakan maupun tidak. kemudian hasil penelitian lanjutan menemukan bahwa pendekatan pembelajaran yang melibatkan Riko the Series menghasilkan hasil belajar yang lebih baik, seperti terlihat dari nilai rata-rata yang lebih tinggi. Namun, saat perbandingan hasil belajar antara kelas eksperimen dan kelas kontrol dilakukan, tidak ditemukan dampak yang signifikan antara keduanya. Untuk mengukur pengaruh secara lebih terperinci, dilakukan perhitungan effect size. Dari hasil perhitungan effect size ditemukan bahwa berdasarkan kriteria effect size Cohen’s D dengan ketentuan bahwa populasi dalam penelitian ini adalah seluruh siswa kelas IV SD Negeri Sukaraja 1 Sumedang. Maka dapat disimpulkan bahwa riko the series berpengaruh rendah terhadap hasil belajar siswa sekolah dasar Negeri Sukaraja 1 Sumedang pada materi siklus air dengan pengaruh sebesar 0,254. Kata kunci: riko the series, sekolah dasar, siklus air DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp784-800